Perceived Support and Sense of Social Belonging in Young Adults Who Have a Parent With a Mental Illness - Villatte, Aude; Piché, Geneviève; Benjamin, Sylvie (Frontiers in Psychiatry, 2022)
This participatory action research explores the perceived social support of youth whose parents have a mental illness during their transition to adulthood. Social support is an important protection factor during this developmental period, but few studies have explored how these young adults perceive their social support. Nor has any study assessed whether participation in a group-based participatory action research project could improve these youth's sense of support. Purpose: 1) identify which aspects of social support these youth spontaneously address when talking about their experiences in Photovoice workshops; 2) explore how participants view these types of workshops as a good way to improve their sense of social support and belonging. Methodology: Ten young adults (nine women and one man) between the ages of 18 and 25 who have at least one parent with a mental illness participated in Photovoice meetings in 2019. These group meetings aimed to explore and share their experiences as young adults whose parents have a mental illness. The testimonies were combined with data obtained from the abbreviated version of the Social Provisions Scale and the Scale of Social Belonging. Results: The quantitative results suggest that participants consider their social support levels to be high, but their qualitative statements highlight low level or absence of parental support in terms of emotional, informative or instrumental levels. They see themselves as an important source of support for their parent and discuss the importance of having other supports figures (romantic partner, employer, friends, sibling, etc.). Conversely, they have difficulty asking for help for various reasons (including fear of stigma). They consider that their participation in this Photovoice project allowed them to feel heard, supported and to develop a sense of belonging to a group. Discussion: To conclude, clinical issues to be considered for psychosocial intervention with young adults of parents with a mental illness are discussed.